Karakteristik kasus kecelakaan di UPT kesmas Tegallalang I Kabupaten Gianyar Bali 2014 - Ida Bagus Candra Pranadhita (DiscoverSys Inc., 2017)
Accidents are unpredictable and can not be anticipated by someone. Generally, accidents can be divided into traffic accidents and occupational accidents. In Indonesia, the mortality rate of traffic accidents are 120 people per day. Meanwhile the current global mortality rate reached 1.24 million per year. In Bali, by the Central Bureau of Statistics of Bali Province in 2013 occurred approximately 2166 cases of accidents with fatalities reached 578 victims and material losses of approximately four billion rupiahs. In 2013, accidents placed at first rank of 10 major diseases by 5579 the number of cases with details of 210 cases of occupational accidents and 5369 cases of traffic accidents. No studies have argued about the characteristics of the cases of accidents, so UPT Kesmas Tegallalang I readiness in handling of accident cases is unknown. This study was descriptive quantitative approached using cross-sectional methode. This research was conducted in the region of UPT Kesmas Tegallalang I on December 2014 – Januray 2015. Population in this study were all accident’s victims were brought to Emergency Room of UPT Kesmas Tegallalang I. The sampling technique used was total sampling with a sample of 1131 people. The instrument used wassecondary data of pattient’s register were brought to Emergency Room of UPT Kesmas Tegallalang I at 2014. Data analysis techniques with descriptive which presented in narrative with table or chart. Characteristic of patients most of this research on male sex (64.8 %), group of young adults age ( 30.8 % ), originated from the village of tegallalang (39.9 %) , with the diagnosis stab wound (28.8 %), did not have the medical intervention (50.4 %) , received antibiotics amoxicilin (67.7 %) .The number of the most cases is in November (104 cases) , the number of cases referred is highest in january (8 cases) .The use of amoxicilin is highest in November , the use of erythomicin is highest in December , the use of anti rabies vaccine is highest in february (13 cases). The emergency department at puskesmas requires the readiness of good in providing services to patients accident victims.